Design and Implementation of Standard Operating Procedures to Enhance Fresh Cow’s Milk Packaging Quality: A Case Study at Rembangan Livestock Breeding Center - Hadi Wulandresta Putri, Diptya; Ayuning Gemaputri, Ariesia; Kashif, Farah (CV. SPDFHarmony, 2025)
ABSTRACT Background: Fresh cow’s milk is a highly perishable commodity due to its high water activity and rich nutrient content, making it an ideal medium for microbial growth. Inefficient packaging processes can compromise quality, safety, and shelf life, leading to product loss and reduced consumer trust. The absence of a structured Standard Operating Procedure (SOP) in packaging operations often results in inconsistent handling and increased defect rates. Aims: This study aimed to design, implement, and evaluate a Standard Operating Procedure (SOP) for the fresh cow’s milk packaging process to improve quality consistency and reduce defects at the Rembangan Livestock Breeding and Forage Center. Methods: A descriptive-quantitative approach was employed, combining observation, interviews, and defect data collection before and after SOP implementation. The SOP was developed through process mapping and validated using expert input. Effectiveness was assessed using Chi-Square analysis to compare defect rates pre- and post-implementation. Results: The SOP encompassed pre-packaging, packaging, and post-packaging procedures, including sanitation, equipment preparation, quality testing, and storage protocols. Implementation reduced product defects from 268 units to 159 units, with Chi-Square analysis confirming a statistically significant improvement in quality consistency (p < 0.05). Conclusion: The structured SOP proved effective in standardizing milk packaging operations, minimizing quality variation, and enhancing safety and hygiene practices. By embedding clear guidelines, role responsibilities, and quality checkpoints, the SOP not only improved operational efficiency but also ensured long-term product integrity. This study underscores the critical role of SOPs in agro-industrial contexts, where perishable products require rigorous handling protocols. The approach can serve as a replicable model for other dairy processing facilities aiming to align with international food safety standards, meet market competitiveness requirements, and achieve sustainable operational excellence. Future research should focus on integrating digital monitoring tools into SOP workflows to further optimize quality control and traceability in dairy supply chains.